A study of dried mandarin (Clementina orogrande) peel applying supercritical carbon dioxide using co‐solvent: Influence on oil extraction, phenolic compounds, and antioxidant activity. Issue 1 (7th November 2021) - Quispe‐Fuentes, Issis; Uribe, Elsa; López, Jéssica; Contreras, Daniella; Poblete, Jacqueline
Abstract: Mandarin ( Clementina orogrande ) peel was dried by vacuum drying (VD) and convective drying (CD). Oil extraction was carried out by supercritical fluid extraction (SFE) using CO2, and CO2 with 5 and 10% ethanol as a co‐solvent The extraction conditions were at 300 and 400 bar, and temperatures of 40 and 50°C, respectively. The total phenolic content (TPC) and antioxidant activity by 2, 2‐diphenyl‐1‐picryl‐hydrazyl (DPPH) and oxygen radical absorbance capacity (ORAC) assays were evaluated. The best extracting condition was obtained using 10% ethanol and at 40 or 50°C. The values of TPC and antioxidant activity by DPPH and ORAC were 19.5 ± 1.8 mg GAE/g, 21.93 ± 1.04, and 33.14 ± 3.24 µmol TE/100 g, respectively. There were identified seven phenolic compounds, where hesperidin was the main flavonoid compound. Thus, the obtained oil extract from dried mandarin peel could be used by the food industry, reducing and giving added value to this waste. Practical applications: Mandarin ( Clementine orogrande ) peel is an important source of polyphenols that are related to beneficial health properties. The presence of polyphenols in mandarin peel may be recovered for adding value to this by‐product. An efficient and friendly process for recovery of those biocompounds is supercritical fluid extraction, being this technology also recommended to obtain essential oils from orange peel and other citruses.